1995
DOI: 10.1152/jn.1995.74.6.2225
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of a slow Ca(2+)-dependent K+ current by intracellular Ca2+ chelators in hippocampal CA1 neurons of rat brain slices

Abstract: 1. In hippocampal CA1 neurons of rat brain slices, a Ca(2+)-dependent slow afterhyperpolarization (sAHP) and underlying K+ current (IsAHP) are activated by Ca2+ influx and presumably reflect the time course of the intracellular Ca2+ signal produced by neuronal stimulation. We tested the hypothesis that when exogenous Ca2+ chelators become the predominant mobile Ca2+ buffer in the neuron, they alter the shape of intracellular Ca2+ signals responsible for IsAHP. The nature of this alteration provides insight int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 0 publications
6
108
1
Order By: Relevance
“…Because BAPTA alters Ca 2ϩ chelation and interferes with intrinsic Ca 2ϩ buffers including Ca 2ϩ -activated K ϩ channels (Lancaster and Batchelor 2000), we expected dye perfusion to make immature neurons highly susceptible to switching their spiking behavior. Indeed, moderate concentrations of OGB-1 BAPTA (50-100 M) always induced switching to PS behavior and enhanced the slow AHP (n ϭ 16; data not shown), consistent with previous reports (Borde et al 1995;Jahromi et al 1999;Lorenzon and Foehring 1995;Schwindt et al 1992;Velumian and Carlen 1999;Zhang et al 1995) and with the relationship between spiking behavior and the Ca 2ϩ -dependent slow AHP (Figs. 3 and 5).…”
Section: Regulation Of Adaptation and Spiking Behaviorsupporting
confidence: 91%
See 2 more Smart Citations
“…Because BAPTA alters Ca 2ϩ chelation and interferes with intrinsic Ca 2ϩ buffers including Ca 2ϩ -activated K ϩ channels (Lancaster and Batchelor 2000), we expected dye perfusion to make immature neurons highly susceptible to switching their spiking behavior. Indeed, moderate concentrations of OGB-1 BAPTA (50-100 M) always induced switching to PS behavior and enhanced the slow AHP (n ϭ 16; data not shown), consistent with previous reports (Borde et al 1995;Jahromi et al 1999;Lorenzon and Foehring 1995;Schwindt et al 1992;Velumian and Carlen 1999;Zhang et al 1995) and with the relationship between spiking behavior and the Ca 2ϩ -dependent slow AHP (Figs. 3 and 5).…”
Section: Regulation Of Adaptation and Spiking Behaviorsupporting
confidence: 91%
“…Consistent with previous studies, we found that the amount of SFA of a cell and therefore its spiking pattern could vary during the course of experiments (Borde et al 1995(Borde et al , 2000Lorenzon and Foehring 1995;Zhang et al 1995). Soon after breaking into whole cell configuration (sometimes as early as 2-3 min after break-in), RS cells often displayed increased adaptation, switching eventually (ϳ5-10 min) to PS behavior.…”
Section: Spiking Behaviorsupporting
confidence: 90%
See 1 more Smart Citation
“…However, in central neurons the involvement of RyRs in the reduction of IsAHP appears to be less evident. The CICR mechanism contributes less to the IsAHP (Kumar and Foster 2004;Van de Vrede et al 2007) or does not participate to generation of IsAHP (Zhang et al 1995). The ryanodine retention loss was observed only when the RyR antagonist was administered immediately after the training session.…”
Section: Discussionmentioning
confidence: 94%
“…For example, the speed with which a chelator binds C a 2ϩ ions (C a 2ϩ association rate) has previously been shown to affect phenomena such as synaptic transmitter release (Adler et al, 1991;Spigelman et al, 1996) and Ca 2ϩ -dependent membrane exitability (Z hang et al, 1995) independently of C a 2ϩ affinity. For example, BAP TA effectively attenuates the release of synaptic transmitter in many preparations in which EGTA (K d , 100 -400 nM) (Harrison and Bers, 1987), a chelator that has a similar C a 2ϩ affinity to BAPTA but that binds C a 2ϩ ions 100 -400 times more slowly (slow K on and K off ), is ineffective (Haraf uji and Ogawa, 1980;Smith et al, 1984;Kao and Tsien, 1988;Adler et al, 1991;Stern, 1992;Winslow et al, 1994;Z hang et al, 1995). To determine whether the effects observed presently on C a 2ϩ waves were affinity-related, rather than being attributable to the C a 2ϩ binding kinetics of the buffers, we tested the effects of EGTA on our preparation.…”
Section: ؉ Affinity Of Exogenous Ca 2؉ Buffers Dictates Their Effectmentioning
confidence: 99%